Possible Worlds of Planet Solaris: The Reader’s Consciousness in the Condition of Indeterminacy - Grebeniuk, T.; Гребенюк, Тетяна Володимирівна (My University, 2020)
The article examines the specifics of the reader’s reception of Stanisław Lem’s novel Solaris in the context of indeterminacy, and the openness of the work to interpretation. The paper examines literary approaches to the formation of meaning in the process of reading this novel, in particular those implemented in Manfred Geier and Istvan Jr. Csicsery-Ronay works. Marie-Laure Ryan’s adaptation of the theory of possible worlds to literary analysis is employed as the methodological basis of my research. On the one hand, the effect of indeterminacy corresponds to the fantastic nature of the conditionality of Lem’s novel. Indeed, the key issue of the work – the encounter of humans with the unknown – requires the author to apply the potential of secrecy. On the other hand, this highly literary work (as well as Andrei Tarkovsky’s film adaptation) is endowed with multiple and ambiguous semantic codes that appeal to the depths of human consciousness and the unconscious. These codes cannot be interpreted unambiguously and, therefore, also provoke a state of uncertainty in the reader. In the textual actual world, semantic codes produce indeterminacy. They are linked to the essence of the single inhabitant of the Solaris, the Ocean, and phantoms created by it who visit the Station. In the novel protagonist’s Kris Kelvin personal world, the state of indeterminacy is associated with the existential essence of his relationship with his beloved Rheya and the problem of making contact with extraterrestrial intelligence. The surreal imagery of Kris’s dreams and visions provide for possible interpretations of the semantic codes of his world.
Keywords: Lem; narrative; possible worlds theory; indeterminacy